ANALISIS YURIDIS TINDAK PIDANA ILLEGAL LOGGING DITINJAU DARI PERBANDINGAN HUKUM INDONESIA, FILIPHINA, DAN MALAYSIA - Erlianto, Reviansyah; Siwi, Galih Raka; Donri, Wahyu (Universitas Ekasakti, 2021)
Globalization certainly has an impact on developments in every country, therefore forest conversion activities are carried out with government permission. In practice, several acts of excessive forest exploitation were found which were classified as criminal acts of illegal logging. The purpose of this study is to understand the existence of the state in forest monitoring and management, and to compare illegal logging crimes in Indonesia, Malaysia, and the Philippines in terms of the laws and regulations of each country. The normative legal research method is in the form of secondary data, the author makes a legal comparison between the laws of the three countries collected through literature study. The results obtained, that the crime of illegal logging is a large and organized crime, in their regulations have condemned all actions related to environmental destruction including illegal logging, weak law enforcement is a factor that causes this crime to be repeated every year.